Navigating the challenges of spectral soil sensing: Key solutions for success - Amin Sharififar; Nicolas Francos; Wartini Ng; Budiman Minasny; Asa Gholizadeh; Senani Karunaratne; Alex McBratney (Soil & Environmental Health)
Diffuse reflectance spectroscopy has emerged as a powerful tool in soil science, providing detailed soil information across diverse landscapes. Its potential to revolutionise soil assessment is immense; however, the path to fully globalise soil spectroscopy is challenging. Researchers aim to harness a global soil spectral library for rapid, accurate, and cost-effective soil evaluation. Yet, there are still operational challenges to be addressed to operationalise soil spectroscopy for routine analysis. We categorise these challenges into four fundamental topics: the standardisation of spectra acquisition, representation and modelling of soil diversity, complexities of soil matrix overlapping effects, and need for temporal monitoring of soils through spectroscopy. First, the variability in measurement protocols and equipment across studies hinders the comparability of results. Establishing standardised methods for spectra acquisition will enhance reproducibility and foster collaboration across the global scientific community. Second, soils are inherently diverse, reflecting a vast array of physical and chemical properties. Capturing this diversity in soil spectral libraries poses a modelling challenge. Comprehensive representation of various soil types and conditions is crucial for the successful application of spectral techniques. Third, the spectral signatures of different soil properties often overlap, complicating the interpretation of spectral data. Understanding and mitigating the effects of matrix interactions are essential for improving the accuracy of soil properties prediction. Fourth, monitoring soil conditions over time is vital for sustainable land management. Developing methodologies that allow for effective temporal assessments using spectroscopy will enhance our understanding of soil dynamics. We explore the advancements made in tackling these challenges and propose innovative solutions aimed at optimising and operationalising soil spectroscopy. By addressing these critical issues, we can pave the way for a future where soil spectroscopy is an integral part of routine soil analysis, enabling scientists and land managers to make informed decisions that promote soil security.